Playing the witch card - Dell'Antonia, K. J. (G. P. Putnam's Sons, 2023)
"Flair Hardwicke knows three things: magic is real, love isn't, and relying on either ends in disaster. So while she's grateful for the chance to take over her grandmother's Kansas bakery after she finally leaves her cheating husband, she won't be embracing Nana's fortune-telling side-hustle. Hers is a strictly no-magic operation--until the innocent batch of Tarot card cookies Flair bakes for the town's Halloween celebration unleashes the power of the family deck, luring Flair's unpredictable mother to town, tempting Flair's magic-obsessed daughter, and bringing back Flair's first love while ensnaring her ex in a curse she can't break. Flair's attempts to control the chaos only make things worse, playing right into the hands of a powerful witch. Suddenly there's far more at stake than her status as the most reluctant witch in town, and the magic Flair has long rejected becomes the only card she has left to play" --